Peran Guru dalam Menstimulasi Perkembangan Motorik Halus Anak PAUD Permata Hati Gunungsari - Naura Zahra Cantika; Wulandari Queenza Amira (Educational Note, 2026)
The development of fine motor skills in early childhood is a crucial aspect in supporting children’s learning readiness and independence in daily activities. The role of teachers as facilitators, motivators, and guides plays a significant part in stimulating fine motor skills through structured and enjoyable activities. This study aims to describe the role of teachers in stimulating the fine motor development of children at PAUD Permata Hati Gunungsari. The research employed a descriptive qualitative method with a case study approach. The research subjects consisted of three teachers and twelve children aged 4–5 years. Data were collected through observation, in-depth interviews, and documentation of learning activities. The findings indicate that teachers actively design and implement various activities involving hand movements and hand–eye coordination, such as bead stringing, cutting, picture matching, playing with modeling clay, and paper folding. Teachers also provide individual guidance and create a pleasant and safe learning environment for children. The strategies applied by teachers have proven effective in stimulating children’s perseverance, focus, and manipulative skills. The study concludes that active and creative teacher involvement in stimulation activities significantly contributes to the development of children’s fine motor skills. Therefore, teacher training in developing fine motor activities needs to be continuously enhanced to optimally support children’s growth and development.